At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Certainly! Let's solve the quadratic equation [tex]\(2x^2 - 8x + 7 = 0\)[/tex] step by step.
1. Form the quadratic equation: The given equation can be expressed in standard form as
[tex]\[2x^2 - 8x + 7 = 0.\][/tex]
2. Identify the coefficients: For the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex],
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -8\)[/tex]
- [tex]\(c = 7\)[/tex]
3. Use the quadratic formula: The quadratic formula states that the solutions to [tex]\(ax^2 + bx + c = 0\)[/tex] are given by:
[tex]\[x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}.\][/tex]
4. Plug in the coefficients: Substitute [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the quadratic formula:
[tex]\[x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4(2)(7)}}{2(2)}.\][/tex]
5. Simplify the expression: Calculate the values inside the formula step by step.
- First, compute [tex]\(-b\)[/tex]:
[tex]\[-(-8) = 8.\][/tex]
- Next, compute [tex]\(b^2\)[/tex]:
[tex]\[(-8)^2 = 64.\][/tex]
- Then, compute [tex]\(4ac\)[/tex]:
[tex]\[4(2)(7) = 56.\][/tex]
- Calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[64 - 56 = 8.\][/tex]
- Compute the square root of the discriminant:
[tex]\[\sqrt{8} = 2\sqrt{2}.\][/tex]
- Put all these into the quadratic formula:
[tex]\[x = \frac{8 \pm 2\sqrt{2}}{4}.\][/tex]
6. Simplify the final expression:
[tex]\[x = \frac{8}{4} \pm \frac{2\sqrt{2}}{4},\][/tex]
[tex]\[x = 2 \pm \frac{\sqrt{2}}{2}.\][/tex]
Therefore, the solutions to the equation [tex]\(2x^2 - 8x + 7 = 0\)[/tex] are:
[tex]\[x = 2 + \frac{\sqrt{2}}{2} \quad \text{and} \quad x = 2 - \frac{\sqrt{2}}{2}.\][/tex]
In decimal form, these solutions are approximately:
[tex]\[x \approx 2.7071 \quad \text{and} \quad x \approx 1.2929.\][/tex]
1. Form the quadratic equation: The given equation can be expressed in standard form as
[tex]\[2x^2 - 8x + 7 = 0.\][/tex]
2. Identify the coefficients: For the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex],
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -8\)[/tex]
- [tex]\(c = 7\)[/tex]
3. Use the quadratic formula: The quadratic formula states that the solutions to [tex]\(ax^2 + bx + c = 0\)[/tex] are given by:
[tex]\[x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}.\][/tex]
4. Plug in the coefficients: Substitute [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the quadratic formula:
[tex]\[x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4(2)(7)}}{2(2)}.\][/tex]
5. Simplify the expression: Calculate the values inside the formula step by step.
- First, compute [tex]\(-b\)[/tex]:
[tex]\[-(-8) = 8.\][/tex]
- Next, compute [tex]\(b^2\)[/tex]:
[tex]\[(-8)^2 = 64.\][/tex]
- Then, compute [tex]\(4ac\)[/tex]:
[tex]\[4(2)(7) = 56.\][/tex]
- Calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[64 - 56 = 8.\][/tex]
- Compute the square root of the discriminant:
[tex]\[\sqrt{8} = 2\sqrt{2}.\][/tex]
- Put all these into the quadratic formula:
[tex]\[x = \frac{8 \pm 2\sqrt{2}}{4}.\][/tex]
6. Simplify the final expression:
[tex]\[x = \frac{8}{4} \pm \frac{2\sqrt{2}}{4},\][/tex]
[tex]\[x = 2 \pm \frac{\sqrt{2}}{2}.\][/tex]
Therefore, the solutions to the equation [tex]\(2x^2 - 8x + 7 = 0\)[/tex] are:
[tex]\[x = 2 + \frac{\sqrt{2}}{2} \quad \text{and} \quad x = 2 - \frac{\sqrt{2}}{2}.\][/tex]
In decimal form, these solutions are approximately:
[tex]\[x \approx 2.7071 \quad \text{and} \quad x \approx 1.2929.\][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.